Impacto do uso de prótese auditiva no índice percentual de reconhecimento de fala em idosos portadores de deficiência auditiva: um ensaio clínico não randomizado - Zanetti, Camila (Universidade do Vale do Rio do Sinos, 2010)
SUBJECT: Clinical practice has demonstrated that elderly users of hearing aids, even when showing decline or worsening of auditory thresholds, maintain or increase the Percentage Index of Speech Recognition through monosyllabic words (PISR), indicating the possible existence of neuronal plasticity in the pertinent areas simultaneously with the improvement of speaking comprehension through continuous stimulation of the hearing system. PURPOSE: to compare the PISR between users and non-users of hearing prosthesis before and after a year of exposure. METHOD: Clinical trial not-randomized with 48 elderly divided in two groups: control group (24 non-users of hearing prosthesis) and intervention group (24 users of hearing prosthesis). The PISR was measured before and after a year of exposure. The elderly were paired according to gender, age and type and degree of hearing loss, thus the difference could demonstrate only the intervention. RESULTS: The elderly users of hearing prosthesis have presented a meaning
Keywords: idoso; Índice Percentual de Reconhecimento de Fala; IPRF; sistema auditivo; prótese auditiva; hearing system; Percentage Index of Speech Recognition; PISR; hearing aids; Ciências da Saúde